Ultrafast Phenomena XVI Proceedings of the 16th International Conference, Palazzo dei Congressi Stresa, Italy, June 9--13, 2008 - Corkum, Paul.; Silvestri, Sandro.; Nelson, Keith A.; Riedle, Eberhard.; Schoenlein, Robert W. (Springer Series in Chemical Physics,, 2009)
Ultrafast Phenomena XVI presents the latest advances in ultrafast science, including both ultrafast optical technology and the study of ultrafast phenomena. It covers picosecond, femtosecond and attosecond processes relevant to applications in physics, chemistry, biology, and engineering. Ultrafast technology has a profound impact in a wide range of applications, amongst them biomedical imaging, chemical dynamics, frequency standards, material processing, and ultrahigh speed communications. This book summarizes the results presented at the 16th International Conference on Ultrafast Phenomena and provides an up-to-date view of this important and rapidly advancing field.